Metabolites of the Anaerobic Degradation of n‐Hexane by Denitrifying Betaproteobacterium Strain HxN1 - Küppers, Julian (Chembiochem, 2019)
The constitutions of seven metabolites formed during anaerobic degradation of n‐hexane by the denitrifying betaproteobacterium strain HxN1 were elucidated by comparison of their GC and MS data with those of synthetic reference standards. The synthesis of 4‐methyloctanoic acid derivatives was accomplished by the conversion of 2‐methylhexanoyl chloride with Meldrum's acid. The β‐oxoester was reduced with NaBH(4), the hydroxy group was eliminated, and the double bond was displaced to yield the methyl esters of 4‐methyl‐3‐oxooctanoate, 3‐hydroxy‐4‐methyloctanoate, (E)‐4‐methyl‐2‐octenoate, and (E)‐ and (Z)‐4‐methyl‐3‐octenoate. The methyl esters of 2‐methyl‐3‐oxohexanoate and 3‐hydroxy‐2‐methylhexanoate were similarly prepared from butanoyl chloride and Meldrum's acid. However, methyl (E)‐2‐methyl‐2‐hexenoate was prepared by Horner–Wadsworth–Emmons reaction, followed by isomerization to methyl (E)‐2‐methyl‐3‐hexenoate. This investigation, with the exception of 4‐methyl‐3‐oxooctanoate, which was not detectable in the cultures, completes the unambiguous identification of all intermediates of the anaerobic biodegradation of n‐hexane to 2‐methyl‐3‐oxohexanoyl coenzyme A (CoA), which is then thiolytically cleaved to butanoyl‐CoA and propionyl‐CoA; these two metabolites are further transformed according to established pathways.